2018
DOI: 10.3390/nu10081104
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning of Geriatric Patients: Is Hypovitaminosis D the Next Marker of Cognitive Dysfunction and Dementia?

Abstract: The study objective is to investigate whether vitamin D is associated with the cognitive function of geriatric patients. This cross-sectional study involved 357 patients hospitalized in the geriatric ward who complained of memory problems (mean age: 82.3 years). The level of cognitive function was measured with the Mini-Mental State Examination (MMSE) and the clinical diagnosis of dementia was established according to the International Classification of Diseases (ICD-10) criteria. The serum 25-hydroxy vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 68 publications
1
11
0
3
Order By: Relevance
“…Considering the body mass index of patients, higher BMI was correlated with a lower probability of having more severe cognitive disorders and this outcome is consistent with a recent study of geriatric patients’ cognitive impairment [ 31 ]. Dye et al [ 32 ] confirm that obesity is associated with impairment of cognitive functions, their accelerated deterioration and dementia in later life.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the body mass index of patients, higher BMI was correlated with a lower probability of having more severe cognitive disorders and this outcome is consistent with a recent study of geriatric patients’ cognitive impairment [ 31 ]. Dye et al [ 32 ] confirm that obesity is associated with impairment of cognitive functions, their accelerated deterioration and dementia in later life.…”
Section: Discussionsupporting
confidence: 90%
“…This is especially apparent in relation to the studies evaluating 25(OH)D 3 serum levels in AD. Substantial evidence shows that vitamin D deficiency is associated with cognitive impairment [70,71,72,73], and an association between low 25(OH)D 3 serum levels and the risk of developing AD has been reported by several authors [54,74,75,76,77]. However, many studies, including those with a long-term follow-up longitudinal design, reported conflicting results [78,79,80].…”
Section: Lacking 25(oh)d3 Standardized Data: the Case Of Alzheimermentioning
confidence: 99%
“…e active form, 1,25(OH)D, binds to the vitamin D receptor (VDR) and influences gene expression. Vitamin D exerts its action via VDR present in neurons, glial cells of the hippocampus, orbitofrontal-cortex, cingulate, amygdala, and thalamus [5][6][7]. Its neuroprotective, anti-inflammatory, and antioxidant effect on neurons promotes brain health [8][9][10].…”
Section: Introductionmentioning
confidence: 99%